Gaps between calcium recommendations to prevent pre-eclampsia and current intakes in one hospital in Argentina - Cormick, Gabriela (2014)
Background: Hypertensive disorders are a major cause of maternal mortality. In Latin America and the Caribbean, pre-eclampsia accounts for approximately one in every four maternal deaths.The World Health Organization recommends calcium supplementation during pregnancy for the prevention and treatment of pre-eclampsia and eclampsia in locations where dietary calcium intake is low. Calcium intake in Argentina is reported to be below WHO recommended levels; however, calcium intake from supplements and water has not been fully evaluated.The objective of this study was to evaluate calcium intake from supplements and water in a group of pregnant women. Methods: This cross-sectional study was conducted at a maternity hospital in the city of Buenos Aires, Argentina. Questionnaires were verbally administered to women attending a routine antenatal care visit. Participants were 18 years of age or older and in their third trimester of pregnancy. Participants were first interviewed to evaluate nutritional supplement consumption and a subgroup was invited to undergo a 24-hour dietary recall. Results: 137 women meeting inclusion criteria consented to participate.The average participant age was 27 years (SD ± 5.9), and all resided in an urban setting. None of the subjects took calcium supplements specifically, although 24 (17%) recalled taking supplements or antacids which contributed to their calcium intake. Mean calcium intake was 663mg SD ±389 for those women completing the 24-hour dietary recall,. This value increased to 706 mg SD ±387 upon considering water intake and measuring chemical composition of water from the areas where women lived at the time of the interview and was further increased to 719 mg (SD ±392) when calcium from supplements was taken into consideration. Conclusions: None of the subjects were consuming calcium supplements. Taking into account the low calcium intake in this population, diverse strategies would be required to comply with recommendations.